Pengaruh Pembiayaan Mudharabah dan Pembiayaan Murabahah Terhadap Laba Bersih Pada Bank Mega Syariah Tahun 2019-2021 - Nisrina Hasna Luthfitah; Wirman Wirman (Peneliti.net, 2023)
This study aims to test how much influence Mudharabah and Murabahah Financing has on Net Profit at Bank Mega Syariah for the 2019-2021 period. The population and sample in this study are the Monthly Financial Statements of Bank Mega Syariah, January 2019- December 2021, which total 36 data. The analytical method used in this study is using descriptive analysis method, classical assumption test, multiple linear regression analysis, hypothesis testing which is processed using SPSS version 22. The results of this study indicate that the independent variable Mudharabah and Murabahah simultaneously influences the dependent variable Profit Clean.financing Mudharabah has no partial effect on net income.financing Murabaha has a partial negative effect on net income.